Pendampingan Pembuatan NIB untuk Kelegalitasan Usaha UMK Syahrini Snack di Lombok Tengah melalui OSS - Komalasari, Husnita; rosikhu, muhammad; adinda putri, destiana; nalurita, indah; saufika hakim maharani, andika ellena; cahyadi, irwan (Insan Kreasi Media, 2023)
NIB is a business identity number, both individuals, business entities, and legal entities issued by OSS system. NIB can be created by new or existing business actors. The Community Service Program (PKM) is implemented at UMK Syahrini Snack located in Sintung Village, Pringgarata District, Central Lombok Regency. The purpose of this activity is to increase public knowledge regarding the importance of NIB for Small Micro Enterprises (UMK) and obtain an NIB certificate. The learning method used in this activity is the lecture method, discussion and work instruction exercises. The results of this activity were an increase in participants' knowledge of socialization materials including business legality, introduction of NIB and OSS, the importance of a business having an NIB, the benefits of an NIB, the requirements and methods for making an NIB and the steps for making an NIB through OSS. Apart from that, the main objective of this activity was to issue the NIB certificate for Small Micro Enterprises (UMK) Syahrini snacks.